Wireless actuation of piezo-elements for the structural health monitoring of carbon-fiber-reinforced-polymers. (March 2016) - Salas, Mariugenia; Focke, Oliver; Herrmann, Axel S.; Lang, Walter
Abstract: The goal of this research is to evaluate wireless actuation of Piezo-Wafer-Active-Sensors (PWAS) to generate Lamb-waves on Carbon-Fiber-Reinforced-Polymers (CFRP). Transmission is done by implementing inductive coupled coils. However, CFRP behaves as an electrical conductor, shielding radio waves with increasing worse effects at higher frequencies. Thus, there is a great interest to evaluate the kilohertz ranges. The actuator node is prepared by combining the PWAS bonded to the surface with an inductive coil and tuning all in resonance by adding passive components. In this way, the actuator receives a windowed-signal at the frequency provided by the coil system. An actuator node is prepared in order to evaluate the power transmission; while three sensors are used to measure the responses from the material. The measurements demonstrate that it is possible to wireless excite Lamb-waves. Finally, preliminary results show the feasibility to determine the presence of structural failure.